Evidence-based severity assessment of the forced swim test in the rat - Becker, Laura; Mallien, Anne Stephanie; Pfeiffer, Natascha; Brandwein, Christiane; Talbot, Steven R.; Bleich, André; Palme, Rupert; Potschka, Heidrun; Gass, Peter (PLOS ONE, 2023)
The forced swim test (FST) is a traditional assay, which has been used for more than 40 years to assess antidepressant effects of novel drug candidates. In recent years, a debate about the test has focused on the assumption that the FST is highly aversive and burdening for the animals because of the earlier anthropomorphic interpretation and designation as a "behavioral despair test". The Directive 2010/63/EU and the German Animal Welfare law require a prospective severity classification of the planned experimental procedures. Still, an objective examination of the animals’ burden in this test has not been performed yet. To fill this gap, we conducted an evidence-based severity assessment of the forced swim test in rats according to a ’standard protocol’ with a water temperature of 25°C. We examined parameters representing the physiological and the affective state, and natural as well as locomotion-associated behaviors in three separate experiments to reflect as many dimensions as possible of the animal’s condition in the test. Hypothermia was the only effect observed in all animals exposed to the FST when using this standard protocol. Additional adverse effects on body weight, food consumption, and fecal corticosterone metabolite concentrations occurred in response to administration of the antidepressant imipramine, which is frequently used as positive control when testing for antidepressant effects of new substances. We conclude that this version of the FST itself is less severe for the animals than assumed, and we suggest a severity classification of ’moderate’ because of the acute and short-lasting effects of hypothermia. To refine the FST according to the 3Rs, we encourage confirming the predictive validity in warmer water temperatures to allow the rats to maintain physiological body temperature.